2017
DOI: 10.1111/acv.12367
|View full text |Cite
|
Sign up to set email alerts
|

Identifying key sites for connecting jaguar populations in the Brazilian Atlantic Forest

Abstract: Networks of protected areas play a key role for large carnivore conservation since habitat fragmentation and population isolation are strong threats for them. We evaluated the contribution of the Protected Jaguar Areas (PJAs) and other forest fragments (1217 patches) to habitat availability and connectivity for jaguars in the Brazilian Atlantic Forest. We used habitat availability indices to rank the PJAs and the forest fragments according to their importance to different aspects of landscape connectivity. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 57 publications
0
4
0
2
Order By: Relevance
“…2 ). However, Saura et al (2017) reported PA connectivity to be much higher in the Amazon than in the Atlantic forest ecoregions of Brazil, agreeing with the modest levels of connectivity for jaguars provided by PAs in the Brazilian Atlantic forests as found by Diniz et al (2017) . Fajardo et al (2014) also found a similar pattern in Peru, with the coastal region having significantly lower levels of protection and PA connectivity than the Amazon region of this country.…”
Section: Discussionmentioning
confidence: 54%
“…2 ). However, Saura et al (2017) reported PA connectivity to be much higher in the Amazon than in the Atlantic forest ecoregions of Brazil, agreeing with the modest levels of connectivity for jaguars provided by PAs in the Brazilian Atlantic forests as found by Diniz et al (2017) . Fajardo et al (2014) also found a similar pattern in Peru, with the coastal region having significantly lower levels of protection and PA connectivity than the Amazon region of this country.…”
Section: Discussionmentioning
confidence: 54%
“…Desafortunadamente ningún trabajo se realizó en El Salvador, Paraguay y Nicaragua. Las principales acciones y tipos de coberturas identificados se relacionan con: a) la conectividad estructural y genética para diferentes especies focales en selvas tropicales (Moraes et al, 2018); b) identificación de sitios clave para la conectividad de poblaciones en mamíferos en bosques (Diniz et al, 2017); c) actualización de áreas naturales protegidas para la conservación de plantas y fauna en peligro de extinción en bosques (Cardoso da Silva et al, 2018); d) construcción de paisajes agrícolas para la conservación de mamíferos terrestres (Hardt et al, 2015).…”
Section: Tópico Conectividad En Servicios Ecosistémicos (Cse)unclassified
“…The equivalent connected area (ECA) index, which can be derived directly from PC, is also useful for comparing temporal changes to landscape connectivity since it represents the size of one habitat patch that would provide the same connectivity probability value as the habitat pattern in the landscape examined [54]. The PC index has been increasingly used in landscape ecological assessments [55][56][57]. PC, its component fractions and ECA have been used in this study to assess changes in habitat availability and connectivity for two species sensitive to urbanization in Stockholm City.…”
Section: Introductionmentioning
confidence: 99%